Numerical Experiments and Analysis of Shock Wave Diffraction around Structures - Ahmed Bagabir; Ahmed Abutaleb (Yanbu Journal of Engineering and Science)
Flows with adverse pressure gradients are more challenging to simulate numerically due to the boundary layer separation. However, the computational fluid dynamics have been used successfully to improve the understanding of the complex fluid dynamics of the transient shock-induced shear layers. The present research tries to investigate the eligibility of the inviscid, viscous (laminar), and turbulent solvers to find which ones reveal realistic results and agree best with the experiments. The solvers are based on the Euler, the Navier-Stokes equations, and the Reynolds averaged Navier-Stokes equations coupled with the SST turbulence model, respectively. A mesh-adaptive high-order AUSM+ numerical scheme is applied. A systematic validation is performed with three cases focusing on the mechanism of the shock wave diffraction and the behavior of the shear layer. They are shock wave diffraction over a backward-facing step, convex 8o sharp splitter, and curved splitter. The investigation reveals that it is crucial to apply a turbulent solver for flows with separation due to the adverse pressure gradient. The lack of viscosity is responsible for the deviation of the inviscid and laminar resolutions from experiments. Moreover, the CFD simulation reveals tiny details about the shock wave diffraction around curved structure not appear in the experimental schlieren and shadowgraph.